Peterson's master the GRE general test (Peterson's, 2018)
Peterson's® Master the GRE® General Test 2018 is the most comprehensive resource for students who want to earn top scores on the GRE® General Test. This comprehensive guide offers 4 full-length practice tests with expert test-prep tips on exam questions PLUS access to 3 additional practice tests online.